2015
DOI: 10.1186/s12917-015-0340-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment into the usage of levetiracetam in a canine epilepsy clinic

Abstract: BackgroundRetrospective studies can complement information derived from double-blinded randomized trials. There are multiple retrospective studies reporting good efficacy and tolerability of the anti-epileptic drug levetiracetam (LEV) in human patients with epilepsy; however, reports of LEV's tolerability and efficacy in dogs with epilepsy remain limited. The purpose of this retrospective study was to describe the use of LEV in a canine epilepsy clinic and determine the long-term efficacy and tolerability of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 42 publications
1
49
0
2
Order By: Relevance
“…It can be administered both i.v. Levetiracetam has been shown to be safe and efficacious in human patients, dogs, and cats [7][8][9][10], and is currently recommended as a second-line therapy in these species based on the results of these studies. Levetiracetam has been shown to be safe and efficacious in human patients, dogs, and cats [7][8][9][10], and is currently recommended as a second-line therapy in these species based on the results of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…It can be administered both i.v. Levetiracetam has been shown to be safe and efficacious in human patients, dogs, and cats [7][8][9][10], and is currently recommended as a second-line therapy in these species based on the results of these studies. Levetiracetam has been shown to be safe and efficacious in human patients, dogs, and cats [7][8][9][10], and is currently recommended as a second-line therapy in these species based on the results of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported good efficacy and tolerability of LEV in human patients with epilepsy [14]. Recent experimental data demonstrated that LEV accesses SV2A through vesicular endocytosis [10,34].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, there is a group of intractable patients who show an impressive response to LEV after failing many antiepileptic drugs [12,13]. Multiple retrospective studies have reported good efficacy and tolerability of LEV in human patients with epilepsy [14]. LEV was developed for use as an add-on therapy in patients with intractable epilepsy [12].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective evaluation of dogs treated at an epilepsy referral center described response rates to successively administered antiepileptic drugs 101. In this study, 32 dogs were given a third‐line drug after failure to respond to phenobarbital and bromide in combination, 27 of which were treated with levetiracetam.…”
Section: When Should a Second Aed Be Started And Which Should Be Used?mentioning
confidence: 99%